A BIBLIOMETRIC STUDY ON CHINESE HERBAL MEDICINE TREATMENT OF CARDIOVASCULAR DISEASES - Huang, Youliang; Deng, Qingqiong; Zhang, Juan; Sajid, Ali; Shang, Xiangang; Zhou, Mingquan (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The aims of this study are to evaluate and summarize the scientific production in the field of Chinese herbal medicine (CHM) treatment of cardiovascular disease (CVD). Methods: A systematic bibliometric search was performed based on the PubMed database covering relative publications between January 1, 1995, and December 31, 2014. Core of the search strategy include the key word cardiovascular disease and the Medical Subject Heading Chinese herbal medicine. The number, type, country, major journals, and research focus of articles were analyzed in accordance with bibliometrics methodologies. Results: The retrieve results were analyzed and described in the form of texts, tables, and graphs. A total of 3,826 articles were identified, 40.28% of which were original articles. All articles were from 50 countries/territories. China was ranked first with 2,258 articles, followed by Japan with 173 articles. 665 articles were published by Zhongguo Zhong Xi Yi Jie He Za Zhi. Conclusion: The publication activity of literature has grown rapidly in the past 20 years, indicating enhanced attention and increasing research input to CHM treatment of CVD. Owing to its great advances in scientific studies, CHM will continue to play an important role in medical research.